The Dynamics of Artificial Intelligence-Based Islamic Religious Education Learning and Its Implications for the Moral Character Formation of Students in the Disruptive Era - Hasan Kholki; Imam Anas Hadi; Isnaeni (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The rapid development of artificial intelligence (AI) has significantly influenced various sectors, including education, particularly in the context of the disruptive era. This study aims to examine the dynamics of AI-based Islamic Religious Education (IRE) learning and its implications for the moral character formation of students. The research employs a qualitative approach through a literature study, drawing on various academic sources such as books, journal articles, and relevant scientific publications. The data collection technique involves systematic documentation and review of literature related to AI in education, IRE learning strategies, and character education. Data analysis is conducted through stages of data reduction, data display, and conclusion drawing to synthesize key findings and identify patterns across the literature. The results indicate that the integration of artificial intelligence in IRE learning provides opportunities for more adaptive, personalized, and interactive learning experiences. However, it also presents challenges, particularly in maintaining the balance between technological advancement and the cultivation of moral and spiritual values. The role of educators remains crucial in guiding students to internalize ethical values, ensuring that technology serves as a tool to support, rather than replace, the process of character formation. In conclusion, AI-based IRE learning in the disruptive era has significant implications for students’ moral character development. It requires a balanced approach that integrates technological innovation with value-based education to foster morally responsible and spiritually grounded individuals.